The ca. 2785–2805 Ma high temperature ilivertalik intrusive complex of southern west Greenland - Næraa, Tomas; Kokfelt, Thomas F.; Scherstén, Anders; Petersson, Andreas (Geosciences, 2018)
Ferroan granitoid intrusions are rare in the Archaean rock record, but have played a large role in the evolution of the Proterozoic crust, particular in relation to anorthosite-mangerite-charnockite-granite suites. Here we discuss the petrogenesis of the ca. 2785–2805 Ma ferroan Ilivertalik Intrusive Complex, which has many geochemical similarities to Proterozoic iron rich granitoids. We present major and trace element whole rock chemistry and combined in-situ zircon U-Pb, Hf and O isotope data. The intrusive complex divides into: (i) minor tabular units of mainly diorite-tonalite compositions, which are typically situated along contacts to the host basement and (ii) interior larger, bodies of mainly granite-granodiorite composition. Geochemically these two unites display continuous to semi-continuous trends in Haker-diagrams. Whole rock REE enrichment display increases from Yb to La, from 10–25 to 80–100 times chondrite, respectively. The diorite-tonalite samples are generally more enriched in REE compared to the granite-granodiorite samples. The complex has hafnium isotope compositions from around +1.5 to −2.5 epsilon units and δ18O compositions in the range of 6.3 to 6.6‰. The complex is interpreted to be derived from partial melting in a crustal source region during anomalously high crustal temperatures.